AN EXPLORATORY REVIEW ON THE ATTITUDES AND PERCEPTION OF KEY HEALTH WORKERS ON HEALTH PROMOTION AND HEALTH EDUCATION IN UAE - Bin Ishaq., S.A.M. (Emirates Journal of Food and Agriculture, 2017)
Please see the scanned pdf version in full text